Antibacterial Properties Of Laser Surface-Textured TiO2/ZnO Ceramic Coatings - Yusuf, Yusliza; Ghazali, Mariyam Jameelah; Abdollah, Mohd Fadzli; Otsuka, Yuichi; Ohnuma, Kiyoshi; Nakamura, Susumu; Morakul, Sarita (Elsevier Ltd, 2020)
Bacterial attachment on surfaces cause fouling, which reduces the hygiene status and effectiveness of equipment. Preventing bacterial attachment on surfaces through surface modification is a potential solution to fouling and has thus become a key research area. In this study, the effect of different ZnO contents (wt%) and picosecond laser surface texturing on the antibacterial properties of TiO2/ZnO ceramic coatings were investigated. The attachment and viability of Escherichia coli (E. coli) bacteria on laser surface-textured and non-textured TiO2/ZnO ceramic coatings were explored. Bacterial growth in an immersion suspension was evaluated using the optical density method. The number of colony-forming units on laser surface textured TiO2/ZnO coatings was found to be lower than that on non-textured coatings, which indicates that laser surface-textured coatings demonstrate strong antibacterial properties. Furthermore, the number of viable E. coli bacteria on laser surfacetextured TiO2/ZnO coatings was observed to be lower than that on non-textured coatings. This finding also demonstrates that laser surface texturing enhances the antibacterial properties of TiO2/ZnO coatings. Overall, laser surface texturing increased the surface areas of the coatings and improved the effectiveness of ZnO as an antibacterial agent. These results prove that laser surface texturing is a successful method for fabricating antibacterial surfaces